2001
DOI: 10.21273/hortsci.36.5.922
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Concentration of Hydrogen Cyanamide Affect Blueberry Bud Development and Flower Mortality

Abstract: The effects of hydrogen cyanamide (H2CN2) sprays on vegetative and reproductive bud growth and development were evaluated for `Climax' rabbiteye (Vaccinium ashei Reade) and `Misty' southern highbush blueberry (V. corymbosum L. hybrid). `Climax' plants were sprayed with 0% or 1% H2CN2 (v/v) at each of several time intervals or flower bud growth stages following either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The numbers of lateral vegetative budbreaks per centimeter of shoot length were increased by hydrogen cyanamide sprays for both cultivars and in both years (Tables 1-3). This result was expected and is consistent with known responses of southern highbush blueberry to hydrogen cyanamide (Williamson et al, 2001(Williamson et al, , 2002. In Expt.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The numbers of lateral vegetative budbreaks per centimeter of shoot length were increased by hydrogen cyanamide sprays for both cultivars and in both years (Tables 1-3). This result was expected and is consistent with known responses of southern highbush blueberry to hydrogen cyanamide (Williamson et al, 2001(Williamson et al, , 2002. In Expt.…”
Section: Resultssupporting
confidence: 91%
“…Hydrogen cyanamide has been used in blueberry production in the southeast United States to stimulate leaf growth and advance the ripening date of blueberries Williamson et al, 2001Williamson et al, , 2002. During these earlier experiments, observations revealed that poorly timed hydrogen cyanamide applications resulted in significant flower bud mortality, even though leaf growth was readily stimulated.…”
mentioning
confidence: 99%
“…Emergence of 'Rebel' leaves has been excellent, even after mild winters. This is important because many southern highbush blueberries grown in the low-chill areas of the southeastern United States have poor leaf development (Lyrene and Williamson, 1997;Williamson et al, 2001). 'Rebel' plants are highly branched, producing an abundance of fruiting wood.…”
Section: Origin and Descriptionmentioning
confidence: 99%
“…Dormex™ (50% hydrogen cyanamide) has shown potential in accelerating leaf and floral bud development of some fruit crops; so research was conducted to determine its usefulness on blueberries (Williamson et al, 2001(Williamson et al, , 2002. Table 10 shows results from an experiment that was conducted to examine the effects of timing of Dormex applications on 'Climax' rabbiteye blueberry (Williamson et al, 2001).…”
Section: Enhancing Spring Leaf Developmentmentioning
confidence: 99%
“…Table 10 shows results from an experiment that was conducted to examine the effects of timing of Dormex applications on 'Climax' rabbiteye blueberry (Williamson et al, 2001). Plants were artificially subjected to low (270 hrs below 7°C) and moderate (600 hrs below 7°C) chilling conditions and were placed under greenhouse conditions to force vegetative and floral buds.…”
Section: Enhancing Spring Leaf Developmentmentioning
confidence: 99%